2018
DOI: 10.3233/jad-171020
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of SIRT1 Attenuates the Level of Oxidative Stress in the Brains of APP/PS1 Double Transgenic Mice and in Primary Neurons Exposed to Oligomers of the Amyloid-β Peptide

Abstract: In the study, we examined whether the silent information regulator 1 (SIRT1) can attenuate oxidative stress in the brains of mice carrying the APP/PS1 double mutation and/or in primary neonatal rat neurons exposed to oligomers of amyloid-β peptide (AβOs). Starting at 4 or 8 months of age, the transgenic mice were treated with resveratrol (RSV, a stimulator of SIRT1) or suramin (an inhibitor) (each 20 mg/kg BW/day) for two months. The primary neurons were exposed to AβOs (0.5 μM) for 48 h and thereafter RSV (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 82 publications
6
41
0
Order By: Relevance
“…Recent research also shows that activation of SIRT1 protects neurons against Aβ1-42-induced disruption of spatial learning, memory, and synaptic plasticity and counteracts the reduction of SIRT1 expression in hippocampus of rats [23]. Moreover, our own findings reveal that activation of SIRT1 attenuates the oxidative stress caused by amyloid-peptide [24]. These observations identify SIRT1 as a promising therapeutic target for overcoming neurodegeneration.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Recent research also shows that activation of SIRT1 protects neurons against Aβ1-42-induced disruption of spatial learning, memory, and synaptic plasticity and counteracts the reduction of SIRT1 expression in hippocampus of rats [23]. Moreover, our own findings reveal that activation of SIRT1 attenuates the oxidative stress caused by amyloid-peptide [24]. These observations identify SIRT1 as a promising therapeutic target for overcoming neurodegeneration.…”
supporting
confidence: 63%
“…B6.Cg-Tg (APPswe, PSEN 1dE9) mice with an 85Dbo/Mmjax background and strain-matched wildtype (WT) mice were purchased from Shanghai Nanfang Biological Technology Development Co., Ltd. APP/PS1 mice were generated and identified as described previously [24], which is a familial model of AD and represents 1% -3% of the disease (96% is sporadic). At four months of age, 27 double-transgenic mice, and 9 age-and gender-matched WT mice were divided randomly into four groups (n=9/per gourp) as follows: the WT group, APP/PS1 group, RSV-treated group and suramin-treated group.…”
Section: Micementioning
confidence: 99%
“…A recent investigation by our own group16 revealed that in comparison to wild-type mice and untreated primary neurons, expression of SIRT1 is significantly lower both in the brains of APP/PS1 mice and neurons exposed to Aβ. In these same systems, increased numbers of senile plaques and a high level of oxidative stress are apparent, changes than can be attenuated by resveratrol (a stimulator of SIRT1), but enhanced by suramin (an inhibitor of SIRT1).…”
Section: Discussionmentioning
confidence: 95%
“…Extracellular senile plaques containing β-amyloid peptide (Aβ), intra-neuronal neurofibrillary tangles, brain atrophy, and loss of neurons are the neuropathological hallmarks of this disease [3,4]. Clear evidence indicates that accumulation of Aβ, a 4-kDa polypeptide formed by proteolytic cleavage of amyloid precursor protein (APP) by βand γ-secretases, is a primary pathogenic event [5,6], leading to synaptic and neuronal loss, oxidative damage, and multiple inflammatory responses [7][8][9].…”
Section: Introductionmentioning
confidence: 99%